2022
DOI: 10.1093/nar/gkac1077
|View full text |Cite
|
Sign up to set email alerts
|

RCSB Protein Data Bank (RCSB.org): delivery of experimentally-determined PDB structures alongside one million computed structure models of proteins from artificial intelligence/machine learning

Abstract: The Research Collaboratory for Structural Bioinformatics Protein Data Bank (RCSB PDB), founding member of the Worldwide Protein Data Bank (wwPDB), is the US data center for the open-access PDB archive. As wwPDB-designated Archive Keeper, RCSB PDB is also responsible for PDB data security. Annually, RCSB PDB serves >10 000 depositors of three-dimensional (3D) biostructures working on all permanently inhabited continents. RCSB PDB delivers data from its research-focused RCSB.org web portal to many million… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
198
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 289 publications
(200 citation statements)
references
References 129 publications
2
198
0
Order By: Relevance
“…We based this approach on the observation that AlphaFold can predict inter-residue distances even for disordered proteins, despite having been trained on folded proteins. This is important because it enables the transfer of inter-residue distance information from folded proteins, whose accurate structures are available in large numbers in the Protein Data Bank (PDB) 19 for the training of deep learning methods, to disordered proteins, whose structural ensembles have been determined in much lower numbers and with less accuracy 20 .…”
Section: Introductionmentioning
confidence: 99%
“…We based this approach on the observation that AlphaFold can predict inter-residue distances even for disordered proteins, despite having been trained on folded proteins. This is important because it enables the transfer of inter-residue distance information from folded proteins, whose accurate structures are available in large numbers in the Protein Data Bank (PDB) 19 for the training of deep learning methods, to disordered proteins, whose structural ensembles have been determined in much lower numbers and with less accuracy 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The returning AlloMAPS database ( 25 ) now encompasses AFDB entries and other new-generation structure predictions, offering improved insights into the impact of mutations on allostery and helping design of allosteric drugs. The RCSB Protein Data Bank ( 26 ) reports that structure predictions, including AFDB, are now available via its website, alongside its core experimentally determined structures which now number almost 200 000. The update from GPCRdb ( 27 ) reports state-specific AF2 models alongside other new features such as lists of ligands for each receptor, both endogenous and surrogate.…”
Section: New and Updated Databasesmentioning
confidence: 99%
“…T6EC1 had no known functional annotation based on its sequence, so we decided to use structural searches to understand its possible activity. We searched the Alphafold2 predicted structure of T6EC1 against PDB using Foldseek, a fast, structure based search algorithm 33,[63][64][65] . This revealed that T6EC1 has a striking structural similarity to Colicin M (PDB: 2XTQ) (Supplementary Figure 9).…”
Section: Supplementary Figure 7 Heterologous Expression Of T6ec1 and ...mentioning
confidence: 99%